Encryption of Color Images with a New Framework: Implementation Using the Elzaki Transformation - Pirdawood, Mardan A.; Kareem, Shadman; Al-Rassam, Omar (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
The significance of image encryption has risen due to the widespread use of images as a key means of sharing data across different applications. Encryption methods are crucial in defending the confidentiality and integrity of valuable image data. This work proposes a novel method of image encryption technique based on the Elzaki transformation and substitution process, which is made possible by the extension of the Maclaurin series coefficients. The image is encrypted using an infinite series of hyperbolic functions and the Elzaki transform; the inverse Elzaki transform is then used to decrypt the image. Using modular arithmetic, the coefficients that result from the transformation are keyed.